Antimicrobial Activity of Natural Dye from Thespisia populea Extract - Shankar, S.; Anand, R.; Ramesh, K. (Asian Journal of Chemistry, 2010)
The bark extract of Thespisia populea was selected to study the antimicrobial activity against four infectious bacteria such as E. coli, Streptococcus sp., S. aureus, S. epidermis and four fungi such as Trichophyton mentogrophyte, T. tonsurans, T. rubrum and Epidermophyton floccosum.